Developments in Information and Knowledge Management Systems for Business Applications Volume 7 - Kryvinska, Natalia; Greguš, Michal; Fedushko, Solomiia (Studies in Systems, Decision and Control, 2023)
XIX, 629 p. 148 illus., 102 illus. in color.